2019
DOI: 10.1515/pac-2019-0208
|View full text |Cite
|
Sign up to set email alerts
|

New syntheses towards C-glycosyl type glycomimetics

Abstract: Glycomimetics are compounds that resemble carbohydrate molecules in their chemical structure and/or biological effect. A large variety of compounds can be designed and synthesized to get glycomimetics, however, C-glycosyl derivatives represent one of the most frequently studied subgroup. In the present survey syntheses of a range of five- and six membered C-glycopyranosyl heterocycles, anhydro-aldimine type compounds, exo-glycals, C-glycosyl styrenes, carbon-sulfur bonded oligosaccharide mimics are described. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…The compounds were selected from non-inhibitory ones to low nanomolar GP inhibitors. Former GP inhibition studies revealed the essential role of the heterocyclic linker between the glucose unit and the distal aromatic moiety [ 21 , 55 , 56 ]. With respect to the latter aromatic group, the 2-naphthyl substituted derivatives 21b – 25b surpassed the phenyl substituted ones 21a – 25a by a factor of approx.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds were selected from non-inhibitory ones to low nanomolar GP inhibitors. Former GP inhibition studies revealed the essential role of the heterocyclic linker between the glucose unit and the distal aromatic moiety [ 21 , 55 , 56 ]. With respect to the latter aromatic group, the 2-naphthyl substituted derivatives 21b – 25b surpassed the phenyl substituted ones 21a – 25a by a factor of approx.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, taking into account that the glucosyl biphenyl derivative B also inhibited the SGLTs [ 43 ], the study of compounds D was also envisaged. Since many of the D type derivatives proved to be potent inhibitors of glycogen phosphorylases (GP) [ 21 , 55 , 56 ], another validated target in combatting T2DM, these compounds may prove the dual-target concept for SGLT-GP which, to the best of our knowledge, has never yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we prepared several 2,6-anhydro-aldonic acid derivatives ( e.g. esters, nitriles, amidines) and used them as starting materials for the synthesis of a variety of C -glycopyranosyl azoles 28–30 and pyrimidines. 31–33…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we prepared several 2,6-anhydro-aldonic acid derivatives (e.g. esters, nitriles, amidines) and used them as starting materials for the synthesis of a variety of C-glycopyranosyl azoles [28][29][30] and pyrimidines. [31][32][33] In the present study, a series of investigations to get C-glucopyranosyl 1,2,4,5-tetrazines (I in Scheme 1) by ring-closing reactions of the above type glucose-based precursors has been envisaged.…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent example is perhaps canagliflozin ( 2 , Figure 1 ), first approved for use in clinical practice in 2014 [ 28 ]. Indeed, C -glucopyranosyl derivatives have been comprehensively studied as potential GP inhibitors by Somsák and coworkers [ 29 ], leading to some of the most potent catalytic-site inhibitors known to date [ 26 , 30 ]. Based on our previous research [ 19 , 25 , 31 ], we decided to extend our work into the family of C -glucopyranosyl, nucleoside-type, molecules.…”
Section: Introductionmentioning
confidence: 99%